Sparse‐Flowering Orchardgrass Represents an Improvement in Forage Quality During Reproductive Growth. Issue 1 (1st January 2014) - Casler, M.D.; Undersander, D.J.; Papadopolous, Y.A.; Bittman, S.; Hunt, D.; Mathison, R.D.; Min, D.H.; Robins, J.G.; Cherney, J.H.; Acharya, S.N.; Belesky, D.P.; Bowley, S.R.; et al.
ABSTRACT: Orchardgrass ( Dactylis glomerata L.) is a major component of many pastures in temperate North America. Early and profuse flowering in pastures is problematic, because livestock refuse to consume flowering stems, prompting many graziers to simply avoid using this species. The objective of this research was to determine the impact of reduced flowering on the quality of harvested forage under two harvest managements of orchardgrass. Six cultivars, three normal cultivars and three sparse‐flowering cultivars (mean panicle density of 141 vs. 61 panicles m⁻ 2, respectively), were evaluated in field experiments at 21 locations in North America under a 3‐cut harvest management. These cultivars were also evaluated at seven locations under a 5‐cut harvest management. Sparse‐flowering cultivars averaged 9% greater crude protein (CP), 3% lower neutral detergent fiber (NDF), 2% greater NDF digestibility, and 2% greater in vitro dry matter digestibility (IVDMD) than normal cultivars. For the two digestibility measures, differential panicle density between the cultivar groups explained a significant portion of variability, indicating that the increase in forage quality was proportional to the decrease in panicle density below a threshold of about 50 panicles m⁻ 2 . Lastly, differences in regrowth forage quality between cultivar groups were smaller, less consistent, and of lesser statistical significance than for first harvest. While selection for sparse flowering in orchardgrass resulted in significant cause‐and‐effect increases in first‐harvest forage quality, these effects were too small to offset the reduced forage yield associated with the sparse‐flowering trait.